Kemitraan dan kerjasama perpustakaan Perguruan Tinggi Negeri - Asmaul Husna (UIN Sumatera Utara, 2017)
This article discusses about partnership or cooperation libraries of State Universities. Librarians who have extensive knowledge can see and take advantage of existing opportunities libraries can be more advanced than we see at this time. With a library partnership can work together, mutually contribute and mutually mutually beneficial. Keywords: partnership, cooperation, libraries